Uji Resistensi Lambdacyhalothrin Terhadap Nyamuk Aedes Aegypti di Wilayah Pelabuhan Laut - Abdurrakhman Abdurrakhman (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2019)
Abstract: Resistance Test of Lambdacyhalothrin on Aedes Aegypti Mosquito In Port Area. Dengue fever is caused by dengue virus which is transmitted to human blood circulation through the bite of the Aedes aegypti mosquito which is transmitted in almost all parts of Indonesia. Aedes vector control is very intense, especially in the use of insecticides and community empowerment in vector habitat environmental management. Factors using improper insecticides can lead to resistance. This study aims to identify insecticide resistant levels of aedes aegypti mosquitoes in the Semayang Port area. This study was an observational study. The research was carried out by taking samples of mosquitoes from the Prapatan sub-district RT 14 Semayang Port working area, Balikpapan Class II KKP. The population of this study is Ae. adult aegypti from pre-mature breeding obtained from a field that inherits the parent's resisitency. The sample of this study was 20 Ae mosquitoes. Adult aegypti each treatment. Mosquitoes for the test material in this study came from larvae obtained from the RT 14 wilker village of Semayang Port where the area is a buffer zone in Semayang which is routinely controlled. The test data was obtained by observing the mortality of test and control mosquitoes after being exposed to 0.05% lambdacyhalothrin for 30 minutes. Of the 20 mosquitoes tested, the number of mosquitoes fell in minutes 1, 5, 10, 20, 30, 1 hour and 24 hours. Aedes aegypti mosquito originating from RT 14 Prapatan Subdistrict, Balikpapan tolerant to lambdacyhalothrin 0.05%.